CONCEPTUAL FRAMEWORK FOR THE PREVENTION AND FORECASTING OF MAJOR DENTAL DISEASES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
. This article provides an analytical review of current scientific literature addressing the effects of adverse occupational and production-related factors on the condition of dental hard tissues and the oral mucosa in individuals with direct exposure to such factors. Special attention is given to the pathogenetic mechanisms involved in the development of dental caries, non-carious tooth lesions, inflammatory periodontal diseases, and disorders of the oral mucosa. The literature data indicate that prolonged exposure to harmful industrial agents contributes to increased systemic sensitization, disruption of local immune defense, and imbalance of oral homeostasis. These changes promote the development of dysbiotic processes within the oral cavity, leading to altered clinical presentation, increased disease severity, and reduced effectiveness of conventional preventive measures. The findings emphasize the importance of an integrated and predictive approach to dental disease prevention in populations exposed to unfavorable production conditions.